Catalytic ozonation of multi-component pharmaceutical mixtures: Kinetic evaluation, molecular interaction, including catalyst structure effects - Tolvanen Pasi; Núñez Núñez Ana Fernanda; Duverger Estéban; Saarinen Nikke; Shahid Abdul; Fale Shey Jude; Saeid Soudabeh; Kråkström Matilda; Kumar Narendra; Eränen Kari; Eklund Patrik C.; Mikkola Jyri-Pekka; et al. (Elsevier BV, 2026)
Removal of pharmaceuticals from wastewater remains a major environmental challenge, requiring efficient and selective Advanced Oxidation Processes (AOPs). Catalytic and non-catalytic ozonation was investigated in a laboratory-scale reactor under optimized flow conditions (500–750 mL min⁻¹, 98 % O₂ feed). Ozonation kinetics of active pharmaceutical ingredient mixtures (APIs) consisting of ibuprofen (IBU), diclofenac (DCF), carbamazepine (CBZ), sulfadiazine (SDZ), and sulfamethoxazole (SFX) (40 mg L⁻¹ each) — was investigated using iron-modified zeolite catalysts, Fe-H-Y and Fe-H-Beta, under semi-batch operations (0.5 g catalyst, 20 °C) in order to correlate degradation and mineralization efficiency with catalyst structure, acidity, and stability. Both catalysts significantly improved the ozone utilization compared to non-catalytic ozonation. Interestingly, Fe-H-Y accelerated initial degradation rate, while the use of Fe-H-Beta resulted in the highest level of mineralization. Adsorption–desorption analysis revealed that the molecular size and polarity controlled the interactions between the pharmaceutical and the catalyst: smaller polar compounds (SDZ, SFX) exhibited stronger adsorption on the catalyst, while bulkier molecules (DCF, IBU) were restricted to external surfaces. Post-reaction characterization confirmed that the Fe-H-Y retained more surface area and exhibited lower Fe leaching, while Fe-H-Beta showed significantly higher carbon deposition. Overall, Fe-H-Y combined rapid kinetics and structural stability, while Fe-H-Beta provided higher mineralization, at the expense of more extensive fouling. The study demonstrated that optimized ozonation conditions, coupled with tailored zeolite catalysts, markedly improve the oxidation efficiency and long-term performance in the oxidation of pharmaceuticals.